FROM THE PAMPAS TO THE WORD:STORYTELLING AS A BRIDGE BETWEEN UNIVERSAL CHILDREN'S LITERATURE AND THE GAUCHO IMAGINATION (REMUNOM, 2026)
Introduction: Oral storytelling enriches children's experiences, expands vocabulary, stimulates imagination, and awakens emotions, representing culture, values, and knowledge that are passed on to the child in a playful way. Objective: To promote the recovery of cultural memories of Gaucho traditionalism, in a playful way, through storytelling adapted from classics of universal children's literature. Methodology: University Extension Project that consisted of the creation, by scholarship holders, of a storytelling channel on YouTube called Poncho de Histórias (Poncho of Stories). The stories were selected and the videos recorded for up to 8 minutes in order not to distract the children's attention. For the recording, two microphones, a ring light, an adjustable tripod, and a cell phone were used. The clothing was typical of Rio Grande do Sul, the traditional dress and the bombacha (gaucho trousers). Results: By December 15th, ten storytelling sessions had been posted, told through simple yet educational language, aimed at children, with content designed to preserve regional culture in a playful way. In total, there were 822 views, and because it's a channel focused on a specific region of the country, the South, and a specific audience from the South—those who appreciate Gaucho traditions—it's believed that the Poncho de Histórias Channel was successful in its purpose.